Spomenik: resurrecting voices in the woods - Kirk, David S.; Durrant, Abigail C.; Kosem, Jim; Reeves, Stuart (MIT Press, 2018)
Spomenik (‘monument) is a digital memorial architecture that transposes in time otherwise hidden cultural memories of atrocity. Spomenik was designed as a simple digital audio guide, embedded in a remote rural location (Kočevski Rog, Slovenia), and working without the infrastructure normally present at national memorial sites. By resurrecting voices and cultural narratives of the deceased, positing them back in to the landscape through digital means, Spomenik opens a dialogue about the events of the past, in relation to networks of the living, exploring the role of voice and agency, as serviced through design in the act of memorialization. We contribute a detailed case study of a design-led inquiry about digital memorialization and digital preservation of cultural heritage, and a reflective account about the nature of legacy and the extent to which it is (and perhaps should be) necessarily bound to networks of collective memory, mediated through designed cultural tools.